Physiological Changes of Wheat Varieties Under Water Deficit Condition - Tasmina, T; Khan, AR; Karim, A; Akter, N; Islam, R (Bangladesh Agronomy Journal, 2017)
The experiment was carried out at the research field of the Department of Agronomy of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during November 2014 to March 2015 to assess and evaluate the physiological derivations of wheat varieties under water deficit condition. The experiment was laid out in a split plot design comprising two water regimes (irrigated or control and water stress) in main plot and three wheat varieties (BARI Gom 25, BARI Gom 26 and Sourav) in sub-plot with four replications. Surface irrigation was applied into the irrigated plots in total growing season but it was applied in water stress plots up to 21 days after sowing after that irrigation was stopped in water stress plots. It was revealed that studied parameters were significantly influenced by water regimes, variety and their interaction. The xylem exudation rate, light interception, SPAD value, leaf water potential, relative water content, water retention capacity was higher in irrigated condition where canopy temperature, water uptake capacity, water saturation deficit higher in water stress condition.The wheat var. BARI Gom 26 showed the highest PAR, SPAD value, leaf water potential, relative water content, water retention capacity where BARI Gom 25 exhibit lowest under water deficit condition. On the other hand, BARI Gom 25 showd the highest canopy temperature, water uptake capacity and water saturation deficit in water deficit condition. Therefore, considering the physiological performance and other characters BARI Gom 26 could be considered preferably for water shortage condition followed by Sourav where BARI Gom 25 was susceptible one. Bangladesh Agron. J. 2016 19(2): 105-114